Kartu Indonesia Pintar sebagai Representasi No Poverty dan Education dalam paradigma Sustainable Development Goals - Rahmatullah, Ahmad Fajar; Rahmatullah, Ahmad Farhan (ijd-demos, 2021)
AbstractSustainable Development Goals (SDGs) is a concept of sustainable development combines aspects of social, economic and environmental 17 sustainable development Goals where the first point is No poverty or no poverty. No poverty to be the first point in the SDGs indicates that all the Countries that signed the Document of the SDGs agreed to see the problem of poverty became a serious problem that must be handled by all Countries in the world. To eradicate poverty of course, every Country has her way each. Interesting things seen in the program which is run by the government of President Jokowi in terms of the alleviation of poverty by through education. The concept of no poverty by way of education is not a new thing.  This study uses the study of a literature review with a focus on the study of how the government program in the fight against poverty through education. This study resulted that the efforts to alleviate poverty through education has been run by the Government of Joko Widodo in the period from the first through the Indonesia Smart Program whereby in the year 2015 until the year 2019 poverty significantly decreased and the school participation rate (APS) is increased. In addition have implemented the goals of the first SGD is no poverty, the government of Joko Widodo also indirectly apply goals to 4, namely Quality Education in Indonesia Smart Program.Keywords : sustainable development goals; no poverty ;education; kartu indonesia pintar.  AbstrakSustainable Development Goals (SDGs) merupakan sebuah konsep pembangunan yang berkelanjutan mengkombinasikan aspek sosial, ekonomi serta lingkungan dengan 17 Tujuan pembangunan berkelanjutan dimana point pertama adalah No poverty atau tanpa kemiskinan. No poverty menjadi point pertama dalam SDGs mengindikasikan bahwa seluruh Negara yang menandatangani Dokumen SDGs sepakat melihat permasalahan kemiskinan menjadi masalah yang serius yang harus di tangani oleh seluruh Negara di dunia. Dalam memberantas kemiskinan tentunya tiap Negara memiliki cara nya masing-masing. Hal menarik terlihat dalam program yang di jalankan oleh pemerintah Presiden Jokowi dalam hal pengentasan kemiskinan dengan cara melalui pendidikan. Konsep pemberantasan kemiskinan dengan cara pendidikan bukan merupakan hal yang baru.  Studi ini menggunakan studi literatur  dengan fokus studi tentang bagaimana program pemerintah dalam upaya pengentasan kemiskinan melalui pendidikan. Studi ini menghasilkan bahwa upaya pengentasan kemiskinan melalui pendidikan telah dijalankan oleh Pemerintahan Joko Widodo pada periode pertamanya melalui Program Indonesia Pintar dimana pada tahun 2015 hingga tahun 2019 kemiskinan  secara signifikan menurun  dan angka partisipasi sekolah (APS) meningkat. Selain telah menerapkan goals pertama SGD yaitu no poverty, disamping itu pemerintahan Joko Widodo juga secara tidak langsung menerapkan goals ke 4 yaitu Quality Education pada Program Indonesia Pintar.Kata kunci:  sustainable development goals; kemiskinan; pendidikan; kartu indonesia pintar.